Similarities and differences of person in English and Uzbek languages - Mustafoyeva Moxlaroyim Alisher qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The examination of the degree of person is a subject of considerable academic interest, as it offers valuable insights into the similarities and differences of person. This article aims to explore the perspectives of both English and Uzbek scholars on this linguistic phenomenom. By delving into relevant theories and drawing upon examples from English and Uzbek literature, we endeavor to compare and contrast the terminologies and approaches employed in each language.